The Coexistence of Familial Mediterranean fever and Fibromyalgia Syndrome: Two Cases Reports - Ercan Tural (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2017)
Familial Mediterranean Fever (FMF) is an autoinflammatory disease caused by mutations in the MEFV gene and characterized by recurrent fever, polyserositis and arthritis. It is transmitted in an autosomal recessive pattern. FMF has been predominantly found in ethnic groups living around the Mediterranean basin (Jews, Arabs, Turks, and Armenians). Although accompanying inflammatory diseases have been reported in FMF, the coexistance of fi bromyalgia syndrome (FMS) is very rare. MEFV gene analysis that the first patient had compound heterozygous mutation (M680I+V726A) and the other patient had heterozygous mutation (M694V). This association will be discussed in this case report.